(untitled) - Clark, Thomas D. (Lexington, Kenturky, 1969)
By the flip of a coin, Thomas Dionysius Clark became intertwined in the vast history of Kentucky. In 1928, Clark received scholarships to both the University of Cincinnati and to the University of Kentucky. Kentucky won the coin toss and the claim to one of the South's eminent historians.
Keywords: Kentucky,United states; History,History